2022
DOI: 10.15244/pjoes/140170
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality Evaluation Based on PCA-PSO-SVM Machine Learning in Xinzhou City, China

Abstract: The scientific evaluation of water quality change trends and pollution characteristics is of great significance to improving the current situation of water resources. The particle swarm optimization support vector machine based on principal component analysis (PCA-PSO-SVM) was used to conduct a comprehensive evaluation of groundwater quality in Xinzhou city, and the results were compared with those of a variety of traditional water quality evaluation methods. The evaluation results show that the water quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…PSO is a global optimisation algorithm that can hold discrete and continuous variables [159,160], while SVR is a regression capability. When used together as a hybrid AI system, PSO and SVR can overcome the limitations of each method and improve the accuracy of groundwater quality predictions [161]. The advantages of using POS-SVR in groundwater quantity management include its ability to handle nonlinear relationships and model complex systems and its ability to provide accurate predictions even when the available data is limited or incomplete.…”
Section: Deep Belief Network (Dbn) and Support Vector Regression (Svr)mentioning
confidence: 99%
“…PSO is a global optimisation algorithm that can hold discrete and continuous variables [159,160], while SVR is a regression capability. When used together as a hybrid AI system, PSO and SVR can overcome the limitations of each method and improve the accuracy of groundwater quality predictions [161]. The advantages of using POS-SVR in groundwater quantity management include its ability to handle nonlinear relationships and model complex systems and its ability to provide accurate predictions even when the available data is limited or incomplete.…”
Section: Deep Belief Network (Dbn) and Support Vector Regression (Svr)mentioning
confidence: 99%
“…The results were related to those of several conventional water quality evaluation techniques. The evaluation's ndings demonstrate how thorough and unbiased the PCA-PSO-SVM-based water quality evaluation model is [31]. A water quality dataset in various locations throughout India was categorized using machine learning techniques like RF, NN, MLR, SVM, and BTM.…”
Section: Introductionmentioning
confidence: 99%
“…Ni Qihang used the SVM based on principal component analysis to comprehensively evaluate the groundwater quality. Compared with the traditional water quality evaluation method, the improved SVM algorithm made up for the shortcomings of the traditional method, and had good stability, higher accuracy and calculation efficiency [7]. Sakaa Bachir used the sequence minimum optimization SVM and random forest algorithm as the benchmark model for predicting the water quality value of river basins, and found that the random forest generated more accurate water quality index prediction, thus revealing the improvement of the early water quality index prediction tool [8].…”
Section: Introductionmentioning
confidence: 99%